Dynamic Henry George Theorem and Optimal City Sizes - Shihe Fu (International Studies of Economics)
ABSTRACT The Henry George Theorem (HGT) in static models states that when a city has an optimal population size, aggregate urban differential land rents exactly cover costs of pure public goods. This paper extends the static HGT to dynamic settings. Through a series of dynamic models, the paper tentatively concludes that the HGT holds in dynamic settings in terms of present value—the present value of urban differential land rents equals the present value of public goods expenditure. In urban economies with congestion externalities or production externalities, the dynamic HGT still holds if externalities are priced correctly.